Réponses

2014-10-10T21:00:23+02:00
1) x=3
AB=2*3+1=6+1=7cm
AF=3+3=6cm

2) aire FECD
=FE*EC=AB*(BC-BE)=AB*(BC-AF)=(2*3+1)*(2*3+1-(3+3))=7*(7-6)=7*1=7cm²

3) FD=AD-AF=AB-AF=(2x+1)-(x+3)=2x+1-x-3=x-2

4) aire FECD=FD*FE=FD*AB=(x-2)(2x+1)

5) AIRE ABCD= AB*BC=(2x+1)(2x+1)=(2x+1)²
AIRE ABEF=AB*AF=(2x+1)(x+3)

6) AIRE FECD= AIRE ABCD-AIRE ABEF= (2x+1)²-(2x+1)(x+3)

7) cest une factorisation
(2x+1)²-(2x+1)(x+3)=(2x+1)(x-2)
merci beaucoup loulakar :)
7) (2x+1)[(2x+1)-(x+3)]=(2x+1)(2x+1-x-3)=(2x+1)(x-2)
j'avais pas fini le 7 ;-)
de rien ;-)